A conceptual database model for the identification of degraded areas and areas proposed for planned revitalisation - Zienkiewicz, Aleksandra; Podciborski, Tomasz Stanisław (Bulletin of Geography. Socio-economic Series, 2021)
For revitalization programs to be effective, territorial governments have to introduce consolidated measures that support the planning, organization and implementation of revitalization measures to benefit local communities and economies, and to alleviate crisis situations in degraded areas. Such measures require unlimited access to data that accurately describe social, economic and environmental conditions. In view of the above, the main aim of this study was to propose a conceptual database model for the identification of degraded areas and areas proposed for planned revitalization under revitalization programs implemented in developed rural areas. The detailed objectives of the presented research were to describe the components of the proposed database and the sources of data for developing municipal revitalization programs. The diagram of the database model supporting the initial stages of revitalization was also presented. The research methodology involved analyses, inference and deduction. A questionnaire survey, conducted among geography, spatial planning, urban development and environmental experts, was used as a research tool in the study. The results of the questionnaire confirmed the validity of the components of the proposed database model.